Remarks on some Ceratocanthinae (Coleoptera: Hybosoridae) in Dominican amber - Poinar, George Jr.; Ballerio, Alberto (Zootaxa, 2017)
A recent phylogenetic analysis of the subfamily Ceratocanthinae (Coleoptera: Scarabaeoidea: Hybosoridae) (Ballerio & Grebennikov 2016) allowed the senior author to re-evaluate the generic placement of Ceratocanthus emarginatus Poinar, 2014, a species recently described from Dominican amber (Poinar 2014). The holotype lacks the enrollment coaptations (see Ballerio & Grebennikov 2016) and the flattened mesotibiae and metatibiae typical of members of the genus Ceratocanthus White, 1842 but has character states found in many species of the genus Germarostes Paulian, 1982. These features are a large, dorsal ocular area with incomplete genal canthus; mesotibiae and metatibiae less flattened than in Ceratocanthus; apical portion of mesotibiae bent inwards; and metatibiae with a distinct apical corbel (see Fig. 1 for ventral view of the holotype). Based on the above, Germarostes emarginatus (Poinar, 2014) new combination is proposed. All of the characters listed above are typical for the species of Germarostes assigned to the subgenus Haroldostes Paulian, 1982. However we hesitate to follow the current view of dividing the genus Germarostes into two subgenera, i.e., Germarostes and Haroldostes (Ocampo & Ballerio 2006), since the distinction between these subgenera is not well defined, as is indicated in the phylogenetic analysis (Ballerio & Grebennikov 2016). Germarostes emarginatus resembles some extant Central American Germarostes species that also have a similar dentate apical portion of the clypeus such as G. farri (Howden, 1970) from Jamaica, G. pecki (Howden, 1970) from Jamaica, G. bidens (Bates, 1887) from Panama and Brazil, G. sinuatus (Bates, 1887) from Central America, and G. nasutus (Bates, 1887) from Mexico.